2021
DOI: 10.1021/acs.jpcb.1c04176
|View full text |Cite
|
Sign up to set email alerts
|

Binding of SARS-CoV-2 Fusion Peptide to Host Endosome and Plasma Membrane

Abstract: During infection the SARS-CoV-2 virus fuses its viral envelope with cellular membranes of its human host. The viral spike (S) protein mediates both the initial contact with the host cell and the subsequent membrane fusion. Proteolytic cleavage of S at the S2′ site exposes its fusion peptide (FP) as the new N-terminus. By binding to the host membrane, the FP anchors the virus to the host cell. The reorganization of S2 between virus and host then pulls the two membranes together. Here we use molecular dynamics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 40 publications
(107 reference statements)
4
44
0
Order By: Relevance
“…All-atom molecular dynamics (MD) simulation performed by Banerjee et al 31 showed that the trimeric unit of SARS-CoV-2 FP (residues 816–855) could effectively trigger the initial stages of membrane fusion within hundreds of nanoseconds. Hummer and co-workers 32 used all-atom MD simulations to study the binding of the SARS-CoV-2 FP (residues 816–855) to cellular membranes, finding that two short amphipathic helices ensure high binding strength of the SARS-CoV-2 FP to the cell membrane. Gorgun et al 33 used the FP segment (residues 798–823) of SARS-CoV-1 S-protein as a template for modeling the membrane binding of SARS-CoV-2 FP (residues 816–841) to the human cellular membrane, revealing three major membrane-binding modes.…”
Section: Introductionmentioning
confidence: 99%
“…All-atom molecular dynamics (MD) simulation performed by Banerjee et al 31 showed that the trimeric unit of SARS-CoV-2 FP (residues 816–855) could effectively trigger the initial stages of membrane fusion within hundreds of nanoseconds. Hummer and co-workers 32 used all-atom MD simulations to study the binding of the SARS-CoV-2 FP (residues 816–855) to cellular membranes, finding that two short amphipathic helices ensure high binding strength of the SARS-CoV-2 FP to the cell membrane. Gorgun et al 33 used the FP segment (residues 798–823) of SARS-CoV-1 S-protein as a template for modeling the membrane binding of SARS-CoV-2 FP (residues 816–841) to the human cellular membrane, revealing three major membrane-binding modes.…”
Section: Introductionmentioning
confidence: 99%
“…To simulate GSDMD NT in its native environment, we designed a plasma membrane mimetic with asymmetric lipid composition. Following our earlier work 54 and Lorent et al, 33 the outer leaflet of our membrane is rich in sphingolipids, phospholipids with PC headgroups and holds very few poly-unsaturated lipids. By contrast, the inner leaflet has a high content of lipids with PE headgroups and mostly polyunsaturated tails.…”
Section: Methodsmentioning
confidence: 83%
“…A recent study from Koppisetti et al asserts that a Ca 2+ may be binding to D843/D849 in SARS-CoV-2 FP (corresponding to D825/D830 in SARS-CoV FP); however, as shown from the simulations in this study and Khelashvili et al , there is a high likelihood that second Ca 2+ ion will bind to D812/D821 (corresponding to the D830/D839 in SARS-CoV-2 FP) for the maximal membrane penetration [23, 25]. Recent NMR studies regarding the membrane interaction with the fusion peptide still have yet to be fully resolved as current models use bicelles [25] and micelles [33], which do not completely capture the composition of the bilayer as was done for the computational modeling shown here; though the model of membrane insertion proposed by Koppisetti et al [25] most aligns with our proposed CoV FP interaction with bilayer ( Fig 8 ). Thus, as shown in Figs 6 and 7 , mutations that creates a high propensity for the Ca 2+ binding mode involving the E821/D825 pair, stabilize peptide conformations that are non-productive for membrane penetration and are found here to inactivate the FP ( Fig 6 ).…”
Section: Discussionmentioning
confidence: 95%